Mes souvenirs 1848-1912 - Massenet, Jules 1842-1912 (Paris Lafitte, 1912)
Autobiographie de Jules Massenet (1842-1912), compositeur français.
Keywords: 19th Century (1801-1900); 20th Century (1901-2000); Biography; Opera; France